Development and Validation of the Infection Prevention Appraisal Scale - Maria Lindberg; Magnus Lindberg (MDPI AG, 2023)
It has been emphasized that future studies aimed at improving adherence to infection prevention guidelines should focus on beliefs in, e.g., self-efficacy. Reliable situation specific measures are needed to measure the phenomenon of self-efficacy, but there seems to be few valid scales available that are suitable for measuring one's belief in self-efficacy regarding infection prevention measures. The purpose of the study was to develop a unidimensional appraisal scale to capture nurses' beliefs in their abilities to practice medical asepsis in care situations. When creating the items, evidence-based guidelines for preventing healthcare-associated infections were used together with Bandura's guide for constructing self-efficacy scales. Face validity, content validity, and concurrent validity were tested in various samples of the target population. Furthermore, dimensionality was evaluated on data collected from 525 registered nurses and licensed practical nurses recruited from the medical, surgical, and orthopaedic wards of 22 Swedish hospitals. The Infection Prevention Appraisal Scale (IPAS) consists of 14 items. Face and content validity were endorsed by target population representatives. The exploratory factor analysis suggested unidimensionality, and the internal consistency was good (Cronbach's alpha 0.83). The total scale score correlated with the General Self-Efficacy Scale, as expected, and supported concurrent validity. The Infection Prevention Appraisal Scale demonstrates sound psychometric properties supporting a unidimensional measure of self-efficacy to medical asepsis in care situations.